Mycobacterial crypto-AcpM as a tool to investigate the consequence of drug binding on its key FAS II partner enzyme HadAB - Singh, Bina K.; Biswas, Rupam; Basak, Amit; Das, Amit K. (Biochimica et biophysica acta. General subjects, 2021)
Background Mycobacterial FASII pathway is governed by the Protein-Protein Interaction mediated dynamics existent between Acyl Carrier Protein and its partner enzymes. The dehydratase HadAB, involved in the third step of FASII synthesis has remained a key target of drugs like Thiacetazone (TAC) and its consequence on AcpM binding is yet to be deciphered. Owing to the transient nature of these interactions, analysing their implications as a drug target has been exhausting. Methods In this context, we have developed an in vitro method to study the effect of thiocarbamide-containing compounds, TAC and SPA0355 (a thiourea analogue) against mycobacterial HadAB. Additionally, by utilizing crypto-ACP (NBD-tagged Acyl Carrier Protein) as a tool of our choice, we attempted at exploring the effect of TAC and SPA0355 on mycobacterial HadAB. Results SPA0355 behaves at par with TAC and undergoes activation in the presence of monooxygenase EthA thus, bringing about a covalent modification in HadA subunit of HadAB. The crypto-ACP method provides insights into the altered substrate housing capability in HadAB associated with the impediment of its AcpM mediated functionality; an outcome attributed to the repercussions associated with the binding of the aforementioned thiourea compounds. Conclusion This investigation has assisted in unveiling a two-step mechanism undertaken by AcpM for interacting with its corresponding partner protein during acyl chain transfer. General significance This study highlights the alterations brought about by drug binding in the interplay between ACP and HadAB. Additionally, this work for the first time establishes the role of SPA0355 as a promising drug candidate against dehydratase HadAB. •crypto-ACP as a tool to explore the effect of Thiacetazone and SPA0355 (thiourea analogue) on mycobacterial HadAB.•In vitro method to monitor the effect of thiocarbamide-containing compounds, TAC and SPA0355 against mycobacterial HadAB.•Inhibition in HadAB’s substrate binding prowess due to the oxidation brought about by the thiourea compounds.•SPA0355 highlighted as a promising drug candidate against dehydratase HadAB.